T-cell lymphoma masquerading as extrapulmonary tuberculosis: case report and review of literature - Ranjan, Piyush (J Family Med Prim Care, 2015)
It is often difficult to establish confirmatory diagnosis in cases of extrapulmonary tuberculosis (TB) because of its paucibacillary nature and difficulty in accessing the involved organs. In several cases, empirical anti-tubercular treatment is started, and the patient is followed-up closely for response. In countries with high prevalence of TB, it is a reasonably good strategy and works most of the times. However, catastrophe may occur when aggressive lymphomas masquerade as TB.